Ð¢ÐµÐ¿Ð»Ð¾Ñ„Ð¸Ð·Ð¸Ñ‡ÐµÑÐºÐ¸Ðµ ÑÐ²Ð¾Ð¹ÑÑ‚Ð²Ð° ÐºÑ€Ð¸Ð¾Ð¿Ñ€Ð¾Ñ‚ÐµÐºÑ‚Ð¾Ñ€Ð¾Ð². V. Ð¢ÐµÐ¿Ð»Ð¾Ð¿Ñ€Ð¾Ð²Ð¾Ð´Ð½Ð¾ÑÑ‚ÑŒ Ð¸ Ñ‚ÐµÐ¼Ð¿ÐµÑ€Ð°Ñ‚ÑƒÑ€Ð¾Ð¿Ñ€Ð¾Ð²Ð¾Ð´Ð½Ð¾ÑÑ‚ÑŒ Ñ€ÑÐ´Ð° ÐºÑ€Ð¸Ð¾Ð¿Ñ€Ð¾Ñ‚ÐµÐºÑ‚Ð¾Ñ€Ð¾Ð² Ð¸ Ð¸Ñ… Ð²Ð¾Ð´Ð½Ñ‹Ñ… Ñ€Ð°ÑÑ‚Ð²Ð¾Ñ€Ð¾Ð² - Todrin, A. F.; Timofeyeva, E. V.; Davydova, E. V. (Publishing House ‘Akademperiodyka’ of the National Academy of Sciences of Ukraine; Institute for Problems of Cryobiology and Cryomedicine, 2024)
The literature data for thermal conductivity and thermal diffusivity values of water, pure cryoprotective agents and their aqueous solutions are summarized. The empirical polynomial equations for calculation of thermal conductivity and thermal diffusivity of water, pure cryoprotective agents and their aqueous solutions depending on temperature are derived. The empirical polynomial equations for aqueous solutions of some cryoprotective agents depending on temperature under fixed concentrations or concentration under fixed temperatures are derived.